THE IMPACT OF BULLYING ON CHILDREN AS A SOURCE OF INSPIRATION FOR CREATING PAINTING WORK - Sunarbawa, I Wayan Cahya; Purnami , Ni Made; Karja, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This study journal/independent project raises the theme of the impact of bullying on children as a source of inspiration for ideas for creating works of art. The problem of bullying still often occurs in educational environments, especially among children. Bullying will have a negative impact on the victim in terms of physical and mental health. The cause of the perpetrator committing acts of bullying is based on several factors; namely, the perpetrator has temperamental behavior, and the second factor is due to the parenting style of parents who use violence. The problem faced is how to apply the concept and how to visualize the meaning contained in a painting. The aim to be achieved in the creation of this work is to determine the impact of bullying on children through creativity and imagination in the form of paintings by combining techniques, styles, symbols, colors, and references to achieve the desired goals and meaning. From the themes above, there are 6 (six) works that can be realized with the titles Bullying, Despair, Anxiety, Anti-Social, Depression, and Self-Harm. It can be concluded that the impact of bullying on children provides inspiration for writers in creating works of painting and developing imaginative ideas, which will become valuable and meaningful works of painting. With the creation of these works of art, it is hoped that they will be able to convey messages of meaning as well as be a medium. education and an overview of the impact of bullying on children.